PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Di Toko Second Murah Galo) - Muhammad Kemby Reforman; M. Noor Army; Janusi Waliamin (Universitas Dharmawangsa, 2023)
Thisstudy aims todetermine the effect ofmarketing mix, product(X1), price(X2), Place(X3) and promotion(X4) on purchasingdecisions (Y) using theanalytical method, multiple linearregression, multiplecorrelation, determination, t test and F Test. Fromthe results ofthe multiple linearregression test, theequation Y = 5.366 + 0.051X1 + 0.293X2 – 0.121X3 + 0.810X4. From results themultiple correlationtest, thevalue (R) = 0.777 is the coefficientinterval 0.60 - 0.799, meaning thatthere isquart correlation between theproduct variables(X1), price(X2), Place(X3) and promotion(X4) on purchasing decisions( Y). From testresults coefficient determination, thevalue of R2 = 0.113 or(11.3%) meansthat togetherproduct (X1), price(X2), Place(X3) and promotion(X4) contribute to the purchasedecision (Y) of R2 0.592 or (59.2%). From results of the t test, the t value ofthe product (X1) is 1.226 with α = 0.222 greaterthan α = 0.05 meaning theproduct (X1) has no effect on the purchasedecision (Y). The value of t calculated price(X2) is 3.822 with α = 0.000 lessthan α = 0.05 meaning thatprice (X2) has a significant effect on purchasingdecisions (Y). t value forPlcae (X3) is - 1.530 with α = 0.128 greater than α = 0.05, meaning thatPlace (X3) has no effect on purchasingdecisions (Y). The t value for promotion (X4) is 9.033 with α = 0.000 lessthan α = 0.05 meaning thatpromotion (X4) has a significant effect on purchasingdecisions (Y). From the testresults Fcount is 53.167 with α = 0.000 smallerthan α = 0.05 means that Ha is accepted. Then simultaneouslproduct (X1), price(X2), Place (X3) and promotion(X4) on purchasingdecisions (Y).